PENGARUH NILAI TUKAR PETANI PANGAN, PETERNAKAN DAN PDB SEKTOR PERTANIAN TERHADAP INDEKS PEMBANGUNAN MANUSIA DI INDONESIA - Maulida, Maulida; Juliansyah, Hijri (LPPM Universitas Malikussaleh - Indonesia, 2024)
This study examines the effect of Farmer's Exchange Rates of Food, Livestock, and Gross Domestic Product of the Agricultural Sector on the Human Development Index in Indonesia in the short and long run. This study uses time series data for 48 quarters from 2010 to 2021. The study employs the Vector Error Correction Model (VECM). The results showed that in the short and long run, the Farmer's Exchange Rates of Food, Livestock, and the Gross Domestic Product of the Agricultural Sector partially had a negative and significant effect on the Human Development Index in Indonesia. The Farmer's Exchange Rates of Food, Livestock, and the Gross Domestic Product of the Agricultural Sector simultaneously had a significant effect on the Human Development Index in Indonesia